Determination of lactic and alactic metabolisms of the anaerobic capacity using oxygen uptake - Rodrigo Poles Urso; Marcos David da Silva-Cavalcante; Carlos Rafaell Correia-Oliveira; Salomão Bueno; Mayara Vieira Damasceno; Adriano Eduardo Lima-Silva; Rômulo Bertuzzi (Universidade Federal de Santa Catarina, 2013)
It has been suggested that the participation of alactic anaerobic metabolism(AAM) in physical activity can be estimated by calculating the fast componentof excess post-exercise oxygen consumption (EPOCFAST). Considering that maximalaccumulated oxygen deficit (MAOD) represents the total amount of energytransferred by anaerobic metabolisms, this study aimed to analyze whethersubtracting EPOCFAST from MAOD (MAODLA-1) provides a satisfactory estimate oflactic anaerobic metabolism (LAM). For this purpose, MAODLA-1 was compared withthe method by which the energy derived from blood lactate accumulation (MAODLA-2)is expressed as oxygen equivalent. Nine active adult men were submitted to fourexperimental sessions: 1) a maximal incremental exercise test until exhaustionon a cycle ergometer to measure the maximal oxygen consumption (VO2max) and theexternal power corresponding to VO2max (WVO2max); 2) and 3) sixconstant-workload tests (3 per session) at intensities below WVO2max; 4) oneconstant-workload test at an intensity corresponding to 110% of W O2max. Themain finding was that both methods (MAODLA-1 e MAODLA-2) that were used toestimate the contribution of LAM in MAOD resulted in similar statistical values(p > 0.05). In addition, percentage values of MAODLA-1 (representing MAL) and EPOCFAST (representing AAM) were approximately 78 and 22%, respectively. Thus,the procedure proposed in this paper may be of interest to future studies onthe contribution of anaerobic components to MAOD.